2018
DOI: 10.1155/2018/7218639
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Uncomplicated Cataract Surgery on Retinal Layer Thickness

Abstract: Purpose Our aim was to assess changes in the total retinal thickness (TRT), total retinal volume (TRV), and retinal layer thickness after uncomplicated cataract surgery. Methods A total of 32 eyes of 32 patients who had undergone uncomplicated phacoemulsification surgery and intraocular lens implantation in one eye were enrolled. Effective phacoemulsification time (EPT) and total energy (TE) were recorded. Thickness and TRV were measured using optical coherence tomography. Data were collected preoperatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…This is similar to the results reported in previous studies in nondiabetic patients. Kurt and Kilic [ 20 ] showed a decrease in MT on the first postoperative day, increases at week 1 and months 1 and 3, and a relative decrease at month 6, although MT did not return to preoperative levels. Zhao et al [ 21 ] also reported that at 1 month and 3 months after surgery, the full retina of the fovea, parafovea, and perifovea increased significantly, and this change was more obvious in the inner layer.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the results reported in previous studies in nondiabetic patients. Kurt and Kilic [ 20 ] showed a decrease in MT on the first postoperative day, increases at week 1 and months 1 and 3, and a relative decrease at month 6, although MT did not return to preoperative levels. Zhao et al [ 21 ] also reported that at 1 month and 3 months after surgery, the full retina of the fovea, parafovea, and perifovea increased significantly, and this change was more obvious in the inner layer.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the pRNFL and the GCC thicknesses are used to diagnose glaucoma and to monitor the course of the disease. Several studies have reported that cataract surgery leads to changes in the GCC and pRNFL thickness values [4][5][6][7][8][9][10] and these changes must be taken into account for patient followup. However, to the best of our knowledge, no study has directly compared the effect of FLACS with "classic" phacoemulsification on GCC values.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible for a patient to suffer significant neural loss before being deemed outside normal limits [ 3 ]. Several studies have reported that GCC and pRNFL thickness parameters significantly increase after cataract surgery [ 4 7 ] with a tendency to decrease with time [ 8 ], although without reaching preoperative levels [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In non-diabetic patients, Kurt A et al [19] showed a decrease in MT at the first postoperative day visit and then increasing at week 1, and months 1 and 3, and then relatively decreasing at month 6 although not returning to preoperative levels. Zhao et al [20] also reported at 1 month and 3 months after surgery, the full retinal the fovea [10] , parafovea, and perifovea increased significantly and this change was is more obvious in the inner layer.…”
Section: Discussionmentioning
confidence: 96%